Examining the AISAS Model and Tourist Citizenship Behaviour in context of Mining Heritage Tourism - Suhud, Usep; Allan, Mamoon; Hoo, Wong Chee; Prompanyo, Manoch (Journal of Ecohumanism, 2024)
Therefore, the objective of the research is to test the effectiveness of the Attention-Interest-Search-Action-Share model in mining heritage tourism but replacing the Action component with tourist citizenship behaviour. This will therefore yield new and key insights because there are few studies conducted in this area. The current study selected 220 tourists through a convenience sampling technique. The gathered data was treated with exploratory factor analysis and structural equation modelling techniques. Confirmatory results found on the acceptance of the first hypothesis, which is Attention Influences Interest, attention becomes very important in ensuring riveting tactics are put in place when promoting mining heritage tourism. The second hypothesis, Curiosity influences Search, is also supported and confirms that only in the condition of a deep level of curiosity, tourists search for information. The third hypothesis is stating that interest influences TCB. The fourth hypothesis postulates that interest influences Share. It supported the sixth hypothesis stating that Search influences TCB. The rejection was of the sixth hypothesis that stated Search influences Share. The seventh theory stated that TCB influences Share, thereby is accepted. These findings bear some significant implications for attaining the sustainable development goals. Precisely, it means that the promotion of mining heritage tourism advances SDG 11—Sustainable Cities and Communities—since this ensures cultural heritage is preserved and contributes to inclusive and sustainable urban development. Likewise, with increased engagement of tourists during citizenship behaviours, this particular act contributes to SDG 12 through the aspect of sustainable tourism and raising awareness. Similarly, the positive experiences that are increasingly wide follow up essentially give rise to SDG 8 through the promotion of tourism as one of the prime movers for improving the economy.